2021
DOI: 10.4012/dmj.2020-462
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repetitive insertion/removal cycles and simulated occlusal loads on retention of denture retainers

Abstract: The purpose of this study was to investigate the effects of repetitive insertion/removal cycle tests on denture retainers with simulated occlusal loads on the retentive force and deformation of clasp. Abutment teeth in the form of mandibular secondary premolars and clasp in the form of Akers clasps were prepared. The retentive force of the clasp on the abutment teeth were evaluated before and after undergoing repetitive insertion/removal cycle tests with or without cyclic loading. Changes in the clasp shape we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 21 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…The potential of AM has been reported in many papers [11][12][13] through comparison with casted clasps. However, they are mainly focused on Co-Cr clasps.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential of AM has been reported in many papers [11][12][13] through comparison with casted clasps. However, they are mainly focused on Co-Cr clasps.…”
Section: Discussionmentioning
confidence: 99%
“…The casting of Co-Cr alloys has been widely used in the medical field [4][5][6]. Several studies have been conducted on the use of AM for the production of Co-Cr clasps, including the evaluation of static bending [7], geometrical accuracy [8,9], surface roughness [9,10], internal porosity [10], and fatigue behavior [11][12][13]. Kato et al [11] measured the retentive force under cyclic loading up to 10 4 cycles, which is a clinically relevant number of cycles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the applied stroke of about 0.25 mm was given in the experiment. The experiments in many studies on the fatigue behaviors are force controlled 18) . Marie et al 21) measured clasp tip distortions as well as the force, and 0.105 mm to 0.319 mm displacement was measured.…”
Section: Discussionmentioning
confidence: 99%
“…Needless to say, the fatigue behavior is important in the design and evaluation of clasp 17) and therefore experimental studies have been carried out 18) . Behr et al 19) investigated the 10-years survival rate of clasp-retained removal partial dentures and revealed that fracture was observed in clasps for 16.1% of patients, which was almost three times higher than other parts such as connectors.…”
Section: Introductionmentioning
confidence: 99%